A study on conservative management on paediatric bone forearm fractures in tertiary care hospital in Cuddalore district - ., Manikandarajan; Raj, Dinesh (International Journal of Research in Orthopaedics, 2019)
Background: Diaphyseal fractures of the radius and ulna are common in the pediatric population. The standard management for pediatric forearm fractures remains conservative management with closed reduction and immobilization with an above elbow plaster cast. Though the fracture unites readily, malunion is very common. Stiffness of joints, compartment syndrome is other complications of conservative management with plaster cast Forearm fractures are common in the pediatric population. These fractures are mostly managed conservatively by means of closed manual reduction and casting. The aim of this study was to reiterate the importance of conservative management in both bone forearm fractures in the pediatric population. Methods: This was a prospective study from a tertiary level trauma center on 70 children up to 14 years of age with both bone forearm fractures from June 2018 to June 2019, cases were obtained from medical records. Data were collected and confirmed by plain X-ray films and medical records. Results: All fractures achieved union at the final visit. More than 90 of diaphyseal forearm fractures achieved exceptional radiological and clinical outcomes and almost no case had a significantly poor outcome. There were significantly reduced angulation deformities before and after treatment (p<0.05). Conclusions: Nonsurgical treatment as a model of management by means of closed reduction and casting is a very well accepted method of treating pediatric diaphyseal forearm fractures.